A man covered a certain distance at some speed. Had he moved 3 kmph faster, he would have taken 40 minutes less. If he had moved 2 kmph slower, he would have taken 40 minutes more. The distance (in km) is:

3 answers

x = distance

y = speed

t = time

t = x / y

Had he moved 3 kmph faster, he would have taken 40 minutes mean:

x / y - x / ( y + 3 ) = 40 / 60 = 20 ∙ 2 / 20 ∙ 3 = 2 / 3

x / y - x / ( y + 3 ) = 2 / 3

If he had moved 2 kmph slower, he would have taken 40 minutes more mean:

x / ( y - 2 ) - x / y = 40 / 60 = 20 ∙ 2 / 20 ∙ 3 = 2 / 3

x / ( y - 2 ) - x / y = 2 / 3

First equation:

x / y - x / ( y + 3 ) = 2 / 3

x ∙ [ 1 / y - 1 / ( y + 3 ) ] = 2 / 3

x ∙ [ 1 ∙ ( y + 3 ) - 1 ∙ y ] / [ y ∙ ( y + 3 ) ] = 2 / 3

x ∙ ( y + 3 - y ) / ( y² + 3 y ) = 2 / 3

x ∙ 3 / ( y² + 3 y ) = 2 / 3

3 x / ( y² + 3 y ) = 2 / 3

Multiply both sides by y² + 3 y

3 x = 2 ∙ ( y² + 3 y ) / 3

3 x = ( 2 y² + 6 y ) / 3

Multiply both sides by 3

9 x = 2 y² + 6 y

Second equation:

x / ( y - 2 ) - x / y = 2 / 3

x ∙ [ 1 / ( y - 2 ) - 1 / y ] = 2 / 3

x ∙ [ 1 ∙ y - 1 ∙ ( y - 2 ) ] / [ y ∙ ( y - 2 ) ] = 2 / 3

x ∙ [ y - ( y - 2 ) ] / ( y² - 2 y ) = 2 / 3

x ∙ ( y - y + 2 ) / ( y² - 2 y ) = 2 / 3

x ∙ 2 / ( y² - 2 y ) = 2 / 3

2 x / ( y² - 2 y ) = 2 / 3

Divide both sides by 2

x / ( y² - 2 y ) = 1 / 3

Multiply both sides by y² - 2 y

x = ( y² - 2 y ) / 3

Multiply both sides by 3

3 x = y² - 2 y

Now you must slove system:

9 x = 2 y² + 6 y

3 x = y² - 2 y

3 x = y² - 2 y

Multiply both sides by 3

9 x = 3 y² - 6 y

9 x = 9 x

2 y² + 6 y = 3 y² - 6 y

y ∙ ( 2 y + 6 ) = y ∙ ( 3 y - 6 )

Divide both sides by y

2 y + 6 = 3 y - 6

Add 6 to both sides

2 y + 6 + 6 = 3 y - 6 + 6

2 y +12 = 3 y

Subtract 2 y to both sides

2 y +12 - 2 y = 3 y - 2 y

12 = y

y = 12 km / h

3 x = y² - 2 y

3 x = 12² - 2 ∙ 12

3 x = 144 - 24

3 x = 120

x = 120 / 3

x = 40 km
thankyou sir.
sir, any other simple way to solve this pblm.
distance = time * speed, so
(t-2/3)(s+3) = ts
(t+2/3)(s-2) = ts

ts - 2/3 s + 3t - 2 = ts
ts + 2/3 s - 2t - 4/3 = ts

-2s+9t = 6
2s-6t = 4

3t = 10
t = 10/3 hr
s =12 km/hr

check: the distance is 40 km; at 12 km/hr that takes 10/3 hr
40km at 15km/hr = 8/3 hr = 10/3 - 2/3
40km at 10km/hr = 4 hr = 10/3 + 2/3